Strategi Kreatif Dinas Perpustakaan dan Kearsipan di Daerah Istimewa Yogyakarta Dalam Membangun Budaya Sadar Tertib Arsip - Agustina, Fitria; Santi, Zuli Erma (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
This study evaluates the implementation of the archive awareness campaign in the Special Region of Yogyakarta (DIY) using a qualitative approach with a descriptive design. Data were collected through in-depth interviews, and document studies, then analyzed interactively. The results indicate that the campaign successfully raised public awareness about the importance of orderly archive management, with high participation rates across various regions. However, several challenges, such as budget constraints, inadequate infrastructure, and a lack of skilled human resources, particularly in digital archive management, still hinder the program's eﬀectiveness and sustainability. To enhance the campaign's success, this study recommends increasing budget allocation, providing human resource training, utilizing information technology, and implementing more systematic monitoring and evaluation. Collaboration among local governments, communities, and related institutions is also deemed crucial to achieving shared goals. The success of this campaign is expected to serve as a model for other regions in raising awareness and improving the quality of archive management, as well as delivering sustainable positive impacts.